ASUHAN KEBIDANAN PEMERIKSAAN FISIK PADA Ny. A IBU HAMIL DENGAN POST DATE DI PUSKESMAS BALOI PERMAI - Tri Ribut Sulistyawati; Rina Marleni; Dian Juni Ekasari; Nova Roza; T.Marliza Fahnawal; Meman Wartiman; Mariyana; Yenni Aryaneta; Astri Yuni Fitri (Universitas Batam, 2023)
Physical examination in pregnancy can be done with several examinations. In general, it includes general examinations and obstetric examinations. General examinations include examinations of the heart and lungs, reflexes, as well as vital signs such as blood pressure, pulse, temperature, and breathing. The general examination in pregnant women aims to assess the general condition of the mother, nutritional status, level of awareness, and the presence or absence of body deformities.obstetric examination is carried out through a glance examination (inspection), raba examination (palpation), hearing check (auscultation), check tap (percussion). The examination is carried out from head to toe, which in its execution is carried out systematically or sequentially.Pregnancy is a natural process experienced by every woman in the reproductive cycle. Pregnancy begins from conception and ends with the beginning of labor. During this pregnancy there are changes, both abdominal, physical and physicology of the mother.